Seq2Net : a relational information visualization solution - Sudipto Shome. (2012)
The advent of faster and more powerful personal computers has resulted in a tremendous amount of growth in fields involving data analysis and processing. The field of Bioinformatics is no different, with an increased focus on the development of new tools to better help research. The field of expression Quantitative Trait Loci (eQTL) analysis has the potential to create conclusive tests for increased propensity towards diseases caused by genetic abnormalities.